Upaya Penurunan Downtime Line Assembly dengan Mengevaluasi Sistem Total Productive Maintenance pada PT. XYZ - Jason Dio Frenatta; Prayonne Adi (Jurnal Titra, 2018)
The purpose of this study is to find the weakness of Total Productive Maintenance (TPM) system on line assembly, so that it can be fixed properly. TPM system that has been fixed is expected to reduce downtime on line assembly at PT. XYZ. The TPM system will be evaluated both technically and practically. Failure Mode Effect Analysis (FMEA) will be used to evaluate the TPM system from a technical point of view, while the fishbone diagram will evaluate it from a practical point of view. Evaluation results will be used to create the new TPM system. Check points that are important but not available yet in the current TPM system will be added. Complaints of worker who related to TPM are also evaluated one by one. Implementation of the new TPM system shows that there is a significant decrease in downtime ratio from 13.08% to 5.74%.